Consumer Preferences for Animal Welfare in China: Optimization of Pork Production-Marketing Chains - Yaoming Liang; Yu Cheng; Yanjie Xu; Gengrong Hua; Zijian Zheng; Hui Li; Li Han (Animals, 2022)
Consumption demands for pork produced by farms that employ strategies to improve animal welfare (“animal welfare pork”) will be an important indicator for predicting domestic pig feeding standards and pork industry development. This paper analyzes consumer preferences for animal welfare pork based on the choice experiment data of 1274 pork consumers in Guangdong province, China. The results show that consumers had a significant preference for animal welfare pork and that they were willing to pay a premium of 2.359–10.477 CNY/500 g (5.27–23.39%) on average. There is heterogeneity in consumer preferences regarding age, education level, and income. Producers of animal-derived products can not only adjust the mix of production conditions to improve pig welfare and innovate contractual arrangements for industry chain stakeholder groups, but they can also develop differentiated marketing strategies for animal welfare products to meet consumer demands for animal welfare.